2001
DOI: 10.1038/sj.ejhg.5200669
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analyses of culture failures by comparative genomic hybridisation (CGH)–Re-evaluation of chromosome aberration rates in early spontaneous abortions

Abstract: Comparative genomic hybridisation (CGH) represents an alternative molecular-cytogenetic technique capable of detecting chromosomal imbalances by reverse fluorescence in situ hybridisation. As the technique uses genomic DNA for assessment it does not rely on metaphase chromosomes in the test material and thus circumvents technical problems associated with tissue culturing. In the present study, we applied CGH to identify chromosome anomalies in 60 spontaneous abortions of the first trimester, that had failed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 47 publications
(26 reference statements)
4
66
1
6
Order By: Relevance
“…In an attempt to overcome these problems other techniques such as fluorescent polymerase chain reaction (Diego-Alvarez et al, 2005), interphase-FISH (Horiuchi et al, 1997;Lebedev et al, 2004, Vorsanova et al, 2005, chromosome-CGH (Daniely et al, 1998;Fritz et al, 2001), MLPA (Diego-Alvarez et al, 2006) and array-CGH have been introduced in the study of POCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to overcome these problems other techniques such as fluorescent polymerase chain reaction (Diego-Alvarez et al, 2005), interphase-FISH (Horiuchi et al, 1997;Lebedev et al, 2004, Vorsanova et al, 2005, chromosome-CGH (Daniely et al, 1998;Fritz et al, 2001), MLPA (Diego-Alvarez et al, 2006) and array-CGH have been introduced in the study of POCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the array-CGH technique is not a suitable tool for detecting ploidy changes, Ballif et al (2006) described the use of a control DNA of a Klinefelter individual as an approach to identify possible ploidy alterations. All papers in the literature on studies using complementary techniques to cytogenetic analysis showed that the contribution of chromosome anomalies to first-trimester fetal losses is much greater than found by conventional cytogenetic analysis, being estimated in up to 70% (Fritz et al, 2001). For instance, when Daniely et al (1998) used chromosome-CGH in cases in which the karyotype found by cytogenetics was normal or could not be obtained due to culture failure, they detected additional numerical and structural anomalies in 8% of the POC from couples with recurrent abortions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The impact of aneuploidy in early embryos is illustrated by the high prevalence of chromosomal abnormalities detected in spontaneous abortions, exceeding 70% in some studies. [21][22][23][24][25][26] Removal of aneuploid embryos during assisted reproductive techniques (PGD of aneuploidy or preimplantation genetic screening) has been proposed as a way to improve success rates. 27 To date, very little is known about the role that sperm aneuploidy plays in infertility or assisted reproduction.…”
Section: Chromosomal Aneuploidymentioning
confidence: 99%
“…The utilization of comparative genomic hybridization (CGH) and interphase fluorescence in situ hybridization (iFISH) has allowed cytogenetic laboratories to evaluate POC samples that have failed to grow. 24,25 In order to determine the impact of these new techniques, an accurate representation of current abnormality rates, which reflect current reproductive trends, is needed to serve as a comparison.…”
mentioning
confidence: 99%